Coordinated Control Strategies for Polymorphic Energy in Hydrogen-Integrated Virtual Power Plants Under the Goal of a Low-Carbon Economy - Siwei Zheng; Guoping Huang; Zhaoxu Luo (Energies)
This study develops a polymorphic energy coordination strategy for virtual power plants (VPPs) to enhance energy efficiency, operational flexibility, and carbon emission reduction. The proposed framework integrates three core components: (1) a tiered carbon trading mechanism enabling precise emission management through dynamic cost optimization; (2) an advanced two-stage power-to-gas (P2G) system combining electrolysis, methanation, and hydrogen fuel cell operations; (3) a mixed-integer linear programming (MILP) model optimized via CPLEX solver for cost-effective decision-making. Case studies demonstrate the strategy’s effectiveness in balancing economic and environmental objectives across multiple operational scenarios, with experimental validation confirming its practical advantages over conventional approaches. The findings offer critical insights for policymakers and energy enterprises pursuing low-carbon transitions.